Exploring the interplay between diet and oral inflammation - Alghamdi, Rahaf A.; Alzamil, Hala A.; Alzamil, Haya A.; Alotaibi, Rawan Y.; Albishi, Sara M.; Sallam, Amro M.; Alhufaiyan, Nasser S.; Alahdal, Esraa M.; Baeesa, Dania A.; Aljohani, Sara M. (International Journal Of Community Medicine And Public Health, 2024)
The relationship between diet and oral inflammation is intricate and significant, influencing overall periodontal health through various mechanisms. Nutritional factors such as vitamins, minerals, and bioactive compounds play pivotal roles in either exacerbating or mitigating inflammatory processes in the oral cavity. Vitamin C, essential for collagen synthesis and tissue repair, along with calcium, critical for bone health, are key nutrients that support periodontal health by reducing susceptibility to gingival inflammation and periodontitis. Polyphenols, abundant in fruits, vegetables, and tea, exhibit strong anti-inflammatory properties that protect against oxidative stress and inflammation in oral tissues. Dietary patterns also have a profound impact on oral health. The Mediterranean diet, rich in fruits, vegetables, whole grains, and healthy fats, has been associated with lower levels of periodontal inflammation due to its high content of antioxidants and polyphenols. Conversely, the Western diet, characterized by high consumption of refined carbohydrates, sugars, and saturated fats, is linked to increased periodontal disease risk, promoting hyperglycemia and insulin resistance that exacerbate inflammatory responses. Vegetarian and plant-based diets, which emphasize the intake of anti-inflammatory and antioxidant-rich foods, are associated with better periodontal health markers, including lower bleeding on probing and reduced periodontal pocket depth. Antioxidants and anti-inflammatory nutrients are crucial in combating oxidative stress and reducing inflammation, essential for maintaining oral health. Vitamin E, coenzyme Q10, omega-3 fatty acids, and green tea polyphenols are particularly beneficial, reducing oxidative damage and inflammation in periodontal tissues. Dietary strategies incorporating these nutrients effectively support oral health and can be part of a comprehensive approach to preventing and managing periodontal disease. Diet plays a critical role in oral health, influencing periodontal inflammation through specific nutrients and overall dietary patterns. Emphasizing the intake of antioxidant-rich and anti-inflammatory foods, while minimizing harmful dietary components, is fundamental in promoting and maintaining periodontal health.